The Influence of Discounts and Free Delivery Cost on Purchasing Decisions for Miliki Hijab Products in E- Commerce Shopee in East Java - Maulana, Fikih; Aminah, Siti (Indonesian Journal of Business Analytics, 2024)
The aim of this research is to determine the effect of discounts and free delivery cost on purchasing decisions for hijab products on Shopee e- commerce in East Java. The population in this study is consumers who own hijabs in East Java who have made purchases through the Shopee application. The sample in this study was 90 respondents. taken using a purposive sampling technique, namely sampling based on criteria. The sample consisted of respondents who had purchased hijab products in East Java via the Shopee application. The data used in this research are primary and secondary data. The analysis technique used in this research is (PLS) with validity testing, reliability testing and hypothesis testing. The results of this research prove that: (1) Discounts have a positive and significant effect on purchasing decisions. (2) Free Delivery Cost has a positive and significant effect on purchasing decisions.